Dietary adaptation to high starch involves increased relative abundance of sucrase-isomaltase and its mRNA in nestling house sparrows - Brun, Antonio (2021)
Dietary flexibility in digestive enzyme activity is widespread in vertebrates but mechanisms are poorly understood. When laboratory rats are switched to a higher carbohydrate diet, the activities of the apical intestinal alpha-glucosidases (AGs) increase within 6-12 h, mainly by rapid increase in enzyme transcription, followed by rapid translation and translocation to the intestine´s apical, brush-border membrane (BBM). We performed the first unified study of the overall process in birds, relying on activity, proteomic, and transcriptomic data from the same animals. Our avian model was nestling house sparrows (Passer domesticus), which switch naturally from a low-starch insect diet to a higher starch seed diet and in whom the protein sucrase-isomaltase (SI) is responsible for all maltase and sucrase intestinal activities. Twenty-four hours after the switch to a high-starch diet, SI activity was increased but not at 12 h post diet switch. SI was the only hydrolase increased in the BBM, and its relative abundance and activity were positively correlated. Twenty-four hours after a reverse switch back to the lower starch diet, SI activity was decreased but not at 12 h post diet switch. Parallel changes in SI mRNA relative abundance were associated with the changes in SI activity in both diet-switch experiments, but our data also revealed an apparent diurnal rhythm in SI mRNA. This is the first demonstration that birds may rely on rapid increase in abundance of SI and its mRNA when adjusting to high-starch diet. Although the mechanisms underlying dietary induction of intestinal enzymes seem similar in nestling house sparrows and laboratory rodents, the time course for modulation in nestlings seemed half as fast compared with laboratory rodents. Before undertaking modulation, an opportunistic forager facing limited resources might rely on more extensive or prolonged environmental sampling, because the redesign of the intestine´s hydrolytic capacity shortly after just one or a few meals of a new substrate might be a costly mistake.